Solidarität in Europa. Die Covid-19-Pandemie als Impuls für eine resilientere grenzüberschreitende Kooperation? - Dittel, Julia; Weber, Florian (Solidarität in Europa - europäische Solidarität. Akten zur 3. Saarbrücker Europa-Konferenz, 2024)
Keywords: COVID-19; Grenzüberschreitende Kooperation; Pandemie; Saar-Lor-Lux

Pandemiekommunikation aus vergleichender Perspektive. Eine exemplarische Studie aus der Großregion - Polzin-Haumann, Claudia; Reissner, Christina (Universität in der Pandemie / L'Université en temps de pandémie, 2023)
Abstract: „Cette contribution propose un regard comparatif sur la communication relative à la pandémie publiée par différentes institutions de la Grande Région. Sont analysés à titre d’exemple des extraits de communiqués du Sommet de la Grande Région, des documents de presse ainsi que les sites web de trois universités sélectionnées. Les analyses révèlent des aspects spécifiques concernant l’approche et la construction discursive de l’espace de vie de la Grande Région, selon le groupe d’acteur·rice·s, la fonction et la date de publication des documents au cours de la pandémie.“
Keywords: COVID-19; Kommunikation; Pandemie; Saar-Lor-Lux; Sprachgebrauch

Das Bild vom Nachbarn – wie die Bewohner die Großregion SaarLorLux wahrnehmen - Scholz, Gundula (Die Großregion SaarLorLux. Anspruch, Wirklichkeiten, Perspektiven, 2023)
Abstract: „Die Großregion SaarLorLux – eine grenzüberschreitende Region im Gebiet von Deutschland, Frankreich, Luxemburg und Belgien – war seit der Teilung des karolingischen Großreichs im Jahre 842 Schauplatz zahlreicher Kriege mit daraus resultierenden Grenzverschiebungen, so dass in diesem Raum heute Menschen mit verschiedenen historischen und kulturellen Hintergründen und Nationalitäten leben. Während Grenzen jahrhundertelang Trennlinien waren, bietet das Leben im Grenzraum heute Möglichkeiten, die Menschen, die im Inneren eines Landes wohnen, nicht genießen können.“
Keywords: Fremdbild; Saar-Lor-Lux; Selbstbild

Die Covid-19-Pandemie als Zäsur für die Großregion. Eine Einordnung aus der Perspektive der Grenzraumforschung - Weber, Florian; Dittel, Julia (Universität in der Pandemie / L'Université en temps de pandémie, 2023)
Abstract: „La pandémie de Covid-19 a mis à rude épreuve les multiples formes d’échanges transfrontaliers au sein de ce que l’on appelle la Grande Région. En effet, les restrictions frontalières mises en place pour limiter les impacts de la pandémie s’opposaient à ce qui, ici, était depuis longtemps devenu la normalité politique, économique et sociale. En s’appuyant sur des hypothèses théoriques et conceptuelles issues des border studies, l’article présente les effets de la pandémie sur la région frontalière franco-germano-belgo-luxembourgeoise et ses habitant·e·s. Les processus de rebordering enclenchés au printemps 2020 ont fortement perturbé les pratiques professionnelles, économiques et quotidiennes transfrontalières. En tant qu’espace d’interdépendance, de zone de contact et de transition, le borderland, avec ses fortes interactions et interdépendances transfrontalières, s’était entre-temps transformé en zone de conflit. Les nouveaux processus de debordering, initiés aussi bien de manière formelle par les responsables politiques que (et avant tout) de manière informelle par les citoyen·ne·s, suggèrent cependant que la crise peut également être considérée comme une chance car elle a permis de sensibiliser à l’égard des régions frontalières. Après les premiers enseignements tirés par les décideur·e·s à l’issue de l’expérience bouleversante de la première vague de la pandémie, il convient d’explorer à l’avenir dans quelle mesure ces enseignements peuvent être valorisés à long terme et comment la coopération transfrontalière peut être rendue plus résistante aux crises.“
Keywords: COVID-19; Grenzüberschreitende Kooperation; Pandemie; Saar-Lor-Lux

Moving from nation into region. Experiences and memories of cross-border dwelling in the Greater Region SaarLorLux - Boesen, Elisabeth (Border experiences in Europe: everyday life - working life - communication - languages, 2020)
Keywords: Grenzarbeitnehmer; Pendler; Regionale Mobilität; Saar-Lor-Lux

Researching forced migrants’ trajectories. Encounters with multilingualism - Kalocsányiová, Erika (Border experiences in Europe: everyday life - working life - communication - languages, 2020)
Keywords: Ausländischer Arbeitnehmer; Luxemburg; Mehrsprachigkeit; Migration; Saar-Lor-Lux

Digital media practices as digital border experiences among French cross-border commuters in Luxembourg - Martin, Corinne (Border experiences in Europe: everyday life - working life - communication - languages, 2020)
Keywords: Grenzarbeitnehmer; Medienkonsum; Neue Medien; Pendler; Regionale Mobilität; Saar-Lor-Lux

Les pratiques du quotidien transfrontalières dans la Grande Région SaarLorLux - Wille, Christian (2019)
Abstract: „This paper analyses everyday practices carried out by the residents of the Saarland, Lorraine, Luxembourg, Rhineland-Palatinate and Wallonia in the neighbouring regions abroad. The key assumption is the consideration that the inhabitants of the Greater Region SaarLorLux define the transborder reality of life of this region through their cross-border performance of everyday practices. Such a socio-constructivist perspective is not interested in what the Greater Region SaarLorLux actually is, but in what ways it is constituted or how it manifests itself in the daily lives of its inhabitants. Therefor the most common cross-border everyday practices, such as shopping for everyday needs, leisure-time shopping, outdoor recreation/tourism, cultural events, as well as visiting friends and family are looked at in greater detail. These observations are based on selected findings from three recent empirical studies of the study region, which have been linked to each other as well as socio-culturally and socioeconomically mapped in order to carve out the spatial organization, the motives and other contextual factors of cross-border everyday practices in the Greater Region SaarLorLux. This approach allows reconstructing mobility flows and spatial emphases in the context of everyday practices and gives insights into the nature of cross-border living realities in the Greater Region SaarLorLux.“
Keywords: Alltag; Einkaufen; Familie; Internationale Mobilität; Saar-Lor-Lux; Tourismus

Grenzen – Identitäten – Heimat. Theoriegeleitete Annäherungen an Konstrukte und Konzepte im „grenzüberschreitenden“ Kontext - Schönwald, Antje; Spellerberg, Annette; Weber, Florian (Border Futures - Zukunft Grenze - Avenir Frontière. Zukunftsfähigkeit grenzüberschreitender Zusammenarbeit, 2018)
Abstract: „Das Leben in Grenzregionen innerhalb der Europäischen Union ist gerade für die jünge- ren Generationen oftmals normal geworden. Das Überschreiten der Grenzen gehört zum Alltag. In den letzten Jahren, bis vor der Flüchtlingskrise, verloren nationalstaatliche Grenzen grundsätzlich im Hinblick auf ihre Durchlässigkeit an Bedeutung. Dennoch sind Grenzen und Grenzziehungen nie bedeutungslos geworden. Nationalstaatliche Politiken und Rahmungen bestimmen grundlegende Ausrichtungen, die diesseits und jenseits von Grenzen spezifische Implikationen mit sich bringen. Hiermit gehen Ein- und Abgren- zungsprozesse einher, (regionale) Identitäten, „Wir“-Gefühle und Fragen nach Heimat. Der Beitrag gibt vor diesem Hintergrund eine theoriegeleitete Einführung in zentrale Konstrukte und Konzepte, die im grenzüberschreitenden Kontext Bedeutung erlangen: Grenze(n) und Grenzziehungen, (raumbezogene und regionale) Identitäten sowie Hei- mat. Am Beispiel der Großregion werden Identifikationsprozesse ausgeleuchtet und ein- geordnet.“
Keywords: Heimat; Regionale Identität; Saar-Lor-Lux

Wohnen jenseits der Grenze. Regionale Integration und ihre lokale Verwirklichung - Boesen, Elisabeth; Schnuer, Gregor (Lebenswirklichkeiten und politische Konstruktionen in Grenzregionen. Das Beispiel der Großregion SaaLorLux. Wirtschaft – Politik – Alltag – Kultur, 2015)
Abstract: „Die Großregion SaarLorLux ist wie kaum eine andere Region Europas durch grenzüberschreitende Bewegungen gekennzeichnet. Sichtbarste Erscheinungsform dieser Mobilität sind die täglichen Pendlerströme nach Luxemburg. Seit einigen Jahren ist als eine weitere Form die grenzüberschreitende Wohnmigration hinzugekommen, die, anders als das Arbeitspendeln, von Luxemburg, dem wirtschaftlichen Zentrum der Region, in die Peripherie, die belgischen, französischen und deutschen Grenzregionen, führt. Eine wesentliche Ursache dieser Entwicklung liegt in den stetig steigenden Preisen für Wohnraum im Großherzogtum. Basierend auf den Ergebnissen einer an der Universität Luxemburg durchgeführten Studie, die sich insbesondere mit der Wohnmigration von Luxemburg in den deutschen Moselraum beschäftigt, wird das Phänomen der grenzüberschreitenden Wohnmigration beleuchtet und mit ähnlichen Erscheinungen in anderen europäischen Regionen verglichen. Der Beitrag liefert einen Einblick in die Vielgestaltigkeit der individuellen sozialen und kulturellen Integrationsprozesse, die mit dieser relativ neuen Mobilitätsform verbunden sind und die trotz ihres numerisch noch relativ geringen Ausmaßes bedeutenden Einfluss auf die regionale Entwicklung und die Verwirklichungen der Großregion SaarLorLux jenseits ihrer politischen Konstruktion haben. Zugleich behandeln die Autoren ausgehend von der Analyse dieser spezifischen Mobilitätserscheinung theoretisch-konzeptuelle Fragen, die für das weitere Feld der borderland studies und der Mobilitätsforschung von Belang sind.“
Keywords: Grenzarbeitnehmer; Regionale Identität; Regionale Mobilität; Regionalentwicklung; Saar-Lor-Lux

Saar-Lor-Lux. Die Bedeutung der lokalen grenzüberschreitenden Kooperation für den europäischen Integrationsprozeß - Schulz, Christian (Europa Regional, 1997)
Abstract: „The intermunicipal, cross-border co-operation in the European border regions has experienced a dynamic thrust of development in the last few years. This was facilitated by the changes in the political, legal and financial framework conditions, to which the community initiative INTERREG provided a considerable contribution. An additional factor in the Saar-Lor-Lux region is that subunits form in the actual border regions within the generously measured, regional work areas of the interregional co-operation, characterised by a fairy homogenous regional structure. Using three case examples, it is demonstrated that cross-border organisation structures have developed within these small regions on a municipal level. These are being institutionalised more and more. Using the regional development model of the network of cities, which is being discussed with regards to its cross-border applicability, we can in this context speak of local co-operation networks. In the case of the Agglomération Transfrontalière du Pôle Européen de Développement (PED) in the Belgian-French-Luxembourg state triangle, the participating local authority districts and government authorities have joined together to form an association and maintain a joint Observatoire de l'Urbanisme, responsible among other things since 1996 for the registration and processing of regional data as well as for the development of land use concepts. The M eeting of Mayors and/or the Ronde des Trois Frontières, responsible for the development of tourism in the German-French-Luxembourg Moselle Valley, are considerably less formal network structures. The co-operation between the border local authority districts was institutionalised in the Saar-Rosselle region in the form of the Intermunicipal Association for Work. The latter maintains a co-operation office with the Saarbrücken city association, principally responsible for co-ordination tasks with regards to current and developing, cross-border projects. Despite the depicted structural and legal impediments, an increased institutionalisation of the co-operations can be observed; this goes hand in hand with a topical diversification, which deincreasingly covers subject areas which have been avoided up until now because of the potential conflicts found therein, as demonstrated by the example of the joint commercial area development in the case of the Agglomération du PED. These observed case examples deal with increasingly integrated core regions within a border region which can provide important impulses for the interregional and also international dialogue. At the same time, practical measures were implemented on this level, which are perceived by the local population in day to day life and therefore have greater identity-forming effects. In this context, these measures can provide an essential or even exemplary contribution to overcoming the interior borders of the EU. These approaches can be understood as being a basis for integration "from the bottom up" which make a greater sustainability and acceptance in the various sectors of day to day living more probable, unlike the top-down forces which dominate the realisation of the European common market or the currency union.“
Keywords: Europäische Integration; Finanzierung; Grenzüberschreitende Kooperation; Netzwerk; Recht; Regionalentwicklung; Saar-Lor-Lux; Stadt; Wirtschaftsförderung